Formulation and antibacterial activity of frankincense sap extract deodorant spray (Styrax benzoin) - Nora Susanti; Jamalum Purba; M Nizam; Cindy Agnesia; Astri Devi Br Pakpahan (Pascasarjana Universitas Negeri Medan, 2023)
Deodorant is a cosmetic preparation used by the wider community to control and reduce body odor. Deodorant act as antibacterial and are able to reduce the excretion of sweat in the armpits. Frankincense is a plant that contains flavonoids and tannins can act as antibacterial. This aim of this study was to determine the effectiveness of frankincense sap extract as an antibacterial in deodorant spray preparation. Frankincense sap powder is macerated with ethanol to obtain frankincense sap extract. Deodorant formulations are prepared from frankincense sap extract in various concentrations (5%, 10%, 15%, 20%, 25%) and combined with cosolvent, emollient, and solvent. Tests carried out include antibacterial testing against Pseuodomonas aureugenisa and Staphylococcus epidermidis bacteria, organoleptic test, pH test, viscosity test, and irritation test. The test results showed that antibacterial testing gave the highest inhibitory diameter of 2.63 mm and 5.35 mm which was exhibited by formulation 5.Keywords: Bacteria; Body odor; Deodorant spray; Styrax benzoin